Let the sequence $(a(n,k))_{ n \in \mathbb{Z}}$ satisfy $$\sum_{j=0}^k c(k,j)a(n-j,k)=0$$ with $c(k,j)=c(k,k-j)$ and $c(k,0)=1$ and with initial values $a(-n,k)=0$ for $1\leq n\leq{k-1}$ and $a(0,k)=1.$

For example for the binomial coefficients $c(k,j)=\binom{k}{j},$ we get $a(n,k)=\binom{-k}{n}.$

Let $A_k(n)$ be the matrix whose entries are $a(n+i+j-k+2,k)$ for $0 \leq i,j \leq {k-2}.$

Computer experiments suggest that $$\det{A_k(n)}=(-1)^{kn+1+\binom{k+1}{2}}a(n,k).$$

A similar result seems to hold if $c(k,j)=-c(k,k-j).$

Any idea how to prove this? Is this a known result or a special case of a more general result?


The question concerns the determinant of a Hankel matrix, or a fixed element of a Hankel matrix transform of a shifted sequence $a(n,k)$ for a fixed $k$, although I do not see how this fact alone can be useful. I give a standalone proof below.

Let $k$ be fixed. For the sake of simplicity, let's denote $c_j := c(k,j)$ and $a_n := a(n,k)$.

First, notice that the sequence $(a_n)$ has the characteristic polynomial $$C(x) := \sum_{j=0}^k c_j x^{k-j},$$ while $C(-x)$ gives the characteristic polynomial for the sequence $((-1)^n a_n)$.

Now, let $b_t(n)$ for $t\in\{0,\dots,k-1\}$ be the determinant of the matrix obtained from the $(k-1)\times k$ matrix: $$\big(a_{n+i+j-k}\big)_{1\leq i\leq k-1\atop 0\leq j\leq k-1}$$ by removing the column with $j=t$. Then $\det A_k(n) = b_0(n) = b_{k-1}(n+1)$.

From the recurrence for $a_n$, it follows that $$ \begin{bmatrix} b_0(n) \\ b_1(n)\\ \vdots\\ b_{k-1}(n) \end{bmatrix} = M\cdot \begin{bmatrix} b_0(n-1) \\ b_1(n-1)\\ \vdots\\ b_{k-1}(n-1) \end{bmatrix},$$ where $$ M := \begin{bmatrix} (-1)^{k-1} c_{k-1} & (-1)^{k-1} c_k & 0 & \dots & 0\\ (-1)^{k-2} c_{k-2} & 0 & (-1)^{k-1} c_k & \dots & 0\\ \vdots & \vdots & \vdots & \ddots & \vdots \\ -c_1 & 0 & 0 & \dots & (-1)^{k-1} c_k\\ 1 & 0 & 0 & \dots & 0 \end{bmatrix}. $$ This is almost a companion matrix and its characteristic polynomial equals the reciprocal of $C((-1)^k x)$, which is same as $C((-1)^k x)$ thanks to the symmetry. In particular, $b_0(n)$ has a characteristic polynomial $C(x)$ when $k$ is even, $C(-x)$ when $k$ is odd.

It remains to notice that $b_0(n)=(-1)^{(k-1)(k-2)/2} a_n$ for $n=-(k-1),\dots, 0$, implying that $\det A_k(n) = b_0(n) = (-1)^{kn + (k-1)(k-2)/2} a_n$. QED

UPDATE. More generally, we can drop the symmetricity requirement $c_j = c_{k-j}$ and keep only $c_0 = c_k$. Then $$\det A_k(n) = (-1)^{kn + (k-1)(k-2)/2} a_{-n-k},$$ where $a_n$ is extended to large negative indices by the same recurrence (see also this answer). This formula implies the original result, since for symmetric $c_j$, we have $a_{-n-k}=a_n$.

Similarly, if we have $c_0 = -c_k$, then $$\det A_k(n) = (-1)^{(k+1)n + (k+1)k/2} a_{-n-k}.$$

  • $\begingroup$ @ Max Alekseyev: Thank you for this very nice proof! $\endgroup$ – Johann Cigler Jan 8 at 7:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.